The influence of inorganic substances on oxidation characteristics of nanopowders - Kwon Y. S.; Amerkovich Yu. A.; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Ilyin A. P. (2005, 2005)
Solid-phase processes at heating (20-1000°C) in the air of aluminium and tungsten nanopowders, produced by electrical explosion of conductors were explored. It was shown the influence of inorganic substances (MnO2, CuSO4·5H2O) on oxidation characteristics of nanopowders: initiation of oxidation temperature, oxidation rate, maximum temperature of exothermic effect by means of differential thermal analysis and thermogravimetry.